Scutellarin Attenuates Microglia-Mediated Neuroinflammation and Promotes Astrogliosis in Cerebral Ischemia - A Therapeutic Consideration - Wu, Chun-Yun; Fang, Ming; Karthikeyan, Aparna; Yuan, Yun; Ling, Eng-Ang (Current Medicinal Chemistry, 2017)
Neuroinflammation plays an important role in different brain diseases including acute brain injuries such as cerebral ischemic stroke and chronic neurodegenerative diseases e.g. Alzheimer's disease etc. The central player in this is the activated microglia, which produce substantial amounts of proinflammatory mediators that may exacerbate the disease. Associated with microglia activation is astrogliosis characterized by hypertrophic astrocytes with increased expression of proinflammatory cytokines, neurotrophic factors, stem cell, neuronal and proliferation markers, all these are crucial for reconstruction of damaged tissue and ultimate restoration of neurological functions. Here, we review the roles of activated microglia and reactive astrocytes in brain diseases with special reference to cerebral ischemia, and the effects of scutellarin, a Chinese herbal extract on both glial cells. We first reviewed the close spatial relation between activated microglia and reactive astrocytes as it suggests that both glial cells work in concert for tissue reconstruction and repair. Secondly, we have identified scutellarin as a putative therapeutic agent as it has been found to not only suppress microglial activation thus ameliorating neuroinflammation, but also enhance astrocytic reaction. In the latter, scutellarin amplified the astrocytic reaction by upregulating the expression of neurotrophic factors among others thus indicating its neuroprotective role. Remarkably, the effects of scutellarin on reactive astrocytes were mediated by activated microglia supporting a functional “cross-talk” between the two glial types. This review highlights some of our recent findings taking into consideration of others demonstrating the beneficial effects of scutellarin on both glial cell types in cerebral ischemia as manifested by improvement of neurological functions.
Keywords: reactive astrocytes